How predictable are the behavioral responses of insects to herbivore induced changes in plants? Responses of two congeneric thrips to induced cotton plants. - Rehan Silva (Public Library of Science (PLoS), 2013)
Changes in plants following insect attack are referred to as induced responses. These responses are widely viewed as a form of defence against further insect attack. In the current study we explore whether it is possible to make generalizations about induced plant responses given the unpredictability and variability observed in insect-plant interactions. Experiments were conducted to test for consistency in the responses of two congeneric thrips, Frankliniella schultzei Trybom and Frankliniella occidentalis Pergrande (Thysanoptera: Thripidae) to cotton seedlings (Gossypium hirsutum Linneaus (Malvales: Malvaceae)) damaged by various insect herbivores. In dual-choice experiments that compared intact and damaged cotton seedlings, F. schultzei was attracted to seedlings damaged by Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), Tetranychus urticae (Koch) (Trombidiforms: Tetranychidae), Tenebrio molitor Linnaeus (Coleoptera: Tenebrionidae), F. schultzei and F. occidentalis but not to mechanically damaged seedlings. In similar tests, F. occidentalis was attracted to undamaged cotton seedlings when simultaneously exposed to seedlings damaged by H. armigera, T. molitor or F. occidentalis. However, when exposed to F. schultzei or T. urticae damaged plants, F. occidentalis was more attracted towards damaged plants. A quantitative relationship was also apparent, F. schultzei showed increased attraction to damaged seedlings as the density of T. urticae or F. schultzei increased. In contrast, although F. occidentalis demonstrated increased attraction to plants damaged by higher densities of T. urticae, there was a negative relationship between attraction and the density of damaging conspecifics. Both species showed greater attraction to T. urticae damaged seedlings than to seedlings damaged by conspecifics. Results demonstrate that the responses of both species of thrips were context dependent, making generalizations difficult to formulate.